The effect of the position of the trimethoxy groups as distant substituents on the spectral and acid sensing properties of phthalocyanines - ODABAŞ, ZAFER (My University, 2022)
In this study, alpha and beta substituted phthalonitrile derivatives were obtained by using 3,4,5-trimethoxyphenol and 2,4,6-trimethoxyphenol, and metal-free and Co2+ phthalocyanine molecules were synthesized using these starting compounds. After the phthalocyanine compounds were purified and characterized by classical methods, their detailed solubility, UV-Vis and FT-IR spectroscopy studies were performed and it was revealed how the positions of methoxy groups changed the spectroscopic properties of phthalocyanines. In addition, during detailed UV-Vis studies of Pcs, it was determined that alpha-substituted Pcs gave an extra peak in 1 x 10(-5) M dichloromethane solution. It was determined that this peak was caused by acid impurities in dichloromethane in trace amounts and UV-Vis spectra in DCM solutions with different trifluoroacetic acid(TFA) concentrations for alpha substituted Pcs (5-8) were studied and their protonation behaviour was examined. It was determined that H2Pc(6) was sensitive to acid even at 1.8 x 10(-3) mM concentration. Thus, acid sensor device can be developed by using this Pc molecule, if desired.
Keywords: Kimya; Fizikokimya; Sıvı Kristaller ve Sıvı Kristal Polimerler; İnorganik Kimya; Temel Bilimler; Chemistry; Physical Chemistry; Liquid Crystals and LCP; Inorganic Chemistry; Natural Sciences; KİMYA, İNORGANİK VE NÜKLEER; Temel Bilimler (SCI); KRİSTALLOGRAFİ; CHEMISTRY, INORGANIC & NUCLEAR; CHEMISTRY; Natural Sciences (SCI); CRYSTALLOGRAPHY; Kimya (çeşitli); Genel Kimya; İnorganik kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Acid sensing; Characterization; Distant substituents; Phthalocyanines; Synthesis; Trimethoxy; ASCORBIC-ACID